Spiritual Neuroscience in the Digital Age: Revitalizing Ethics and Sufism as a Solution for Adolescent Character Development - Jumhur; Dadang (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines how revitalizing Islamic ethics (akhlak) and Sufism (tasawuf) through spiritual neuroscience addresses adolescent character development challenges in digital environments. Using qualitative library research and systematic literature synthesis, we identify neurocognitive vulnerabilities from sustained digital immersion—including disrupted prefrontal maturation, reward sensitization, and attentional fragmentation—that undermine moral reasoning and emotional regulation. Thematic analysis reveals convergences between core Sufi practices (mujāhadah al-nafs, muraqabah, dhikr) and neuroadaptive mechanisms supporting self-regulation, attentional stability, and prosocial orientation. We propose a four-phase framework (Awareness→Regulation→Habituation→Resilience) for embedding neuro-spiritual practices into Islamic education. Findings affirm that sustainable character formation requires holistic interventions engaging cognitive, emotional, social, and spiritual dimensions. Isolated moral instruction or digital literacy initiatives are insufficient without practices cultivating neural-level attentional control, emotional granularity, and ethical habituation. This synthesis bridges Islamic contemplative traditions with neuroscience, highlighting the need for empirical validation of tasawuf-informed interventions to foster morally resilient adolescents in the digital era.